Fatherhood - Santos, Antônio Carlos Flores dos (Scientific Journal of the Foot & Ankle, 2018)
When Dr. Jorge asked me to write something about Professor Egon, given that we are close friends, my first reaction was to feel very honored by the request. I thought it would be easy to talk about our Professor, but it didn’t quite turn out that way. Professor Egon was highly praised at our Congress in Gramado recently, for his work and his legacy of training resident students in Orthopedics at our HC – and previously at the Santa Casa – and in the Traumatology Unit of the HPS, where he was a doctor until his retirement. What’s more, he received the greatest of all homages that anybody could wish for; that of his own son, who literally, followed in his footsteps. It was then that, thinking again, I decided to speak about Prof. Egon and my special relationship with him. I met the Master during the 4th year of my medical course, when he was Chair of General Surgery, Orthopedics discipline, on ward 33 at the Santa Casa de Porto Alegre. It was a theory class, on a Friday morning, which was the curricular time slot for theoretical activities of the Chair on that ward. He had come straight from a night on duty at the Emergency Room of the hospital to the scientific activity, without showing any signs of tiredness. This was the first time I had heard his teachings on the “hallux valgus”, and on its anatomy and physiopathology. His marvelous capacity for description and his teaching methods, which are characteristic to him, seemed to set my very neurons on fire, and I am certain it was then that I, already with a propensity for traumatology, was bitten by the “ambition bug”. I followed him for the rest of the course, whenever I got the chance. In the fifth year, here in Porto Alegre, we took the internship at the HPS for the entire year. In our various shifts between the departments of the Hospital and the days of the week, I found myself, in the second semester, in the Traumatology unit on Thursdays. There, my observation of the Professor’s conduct, both medical and personal, was what most attracted my attention. And care of the traumatological patient demands close attention. He was a good listener, and he was “hands on”, as they say, not only transferring practical skills to the intern students, but also teaching how to do, by doing, and speaking, and explaining the pathology and its course. And so time passed for all of us. We never grew apart. On the contrary, we strengthened family ties, always with a great deal of pride and honor. We were together at most of the Congresses here in the South and those of the ABTPé. We often dined together, and we were always together in the relaxation areas of the Congresses. By together, I mean with our families. When I finally decided on Foot Surgery, at Dr. Mauro’s Congress in Curitiba, in 1992, I joined the SBMCP, with Prof. Egon’s signature as my referee. I have already commented about that time, in one of our Bulletins. Dr. Marcio Benevento, when he received my enrolment form, opened his eyes wide and said: “with this signature here (pointing to the signature), you’re already in! Congratulations!” Unforgettable. We continued to meet at the outpatient clinic of the HC, where I had now graduated from the internship in the IOT in São Paulo. We restarted the Foot Committee in Rio Grande do Sul. We traveled around the state with the whole Committee, presenting themes to update doctor’s knowledge. And amidst all this “youthful” thirst for information and action, there he was, sitting in a van, travelling for three or four hours, from one city to the next, giving his lessons, accompanying everything until the end of the dinners that we were offered, always being searched out, and asked questions about conducts in all types of clinical cases brought by colleagues from the interior of the country. That was the Teacher. He has always been a Teacher. On one of these occasions, I heard him utter a phrase that, at least for me, was one that defines him: “if they invite me to a celebration, I’ll think about it, but if they invite me to a class, a conference or a surgery, I’m ready to go”. I learned that conservative treatment exists, and should be used to its full extent, and that only then should surgery be considered. I also learned that when we go into the theater to perform an operation, the surgery is the most important thing of all; we don’t go into surgery to get it over and done, we go in to perform surgery. And while he was operating, that is exactly what you saw: clean, anatomical surgery, carried out methodically, step-by-step; he was never in a hurry, and he was always talking, explaining and teaching. And that’s what Professor Egon is like, even now. A teacher. A father. An intellectual father to us all.